2000
DOI: 10.1016/s0002-9440(10)64588-9
|View full text |Cite
|
Sign up to set email alerts
|

Fundic Gland Polyps in Familial Adenomatous Polyposis

Abstract: Fundic gland polyps (FGPs) are the most common gastric polyps in both familial adenomatous polyposis (FAP) and sporadic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Furthermore, some case reports have described high-grade dysplasia or adenocarcinoma in association with FAP-associated FGP, suggesting that FAP-associated FGP is a potential premalignant lesion 29 30 31. As for genetic analysis, previous studies revealed the presence of somatic APC mutations in FAP-associated FGP, indicating neoplastic lesions caused by the inactivation of both alleles, similar to the mechanism of other FAP-associated neoplasms 28 32. Consistent with this, 1 patient with 2 noninvasive neoplasms in FGP who underwent proximal gastrectomy in our study had inactivation of the APC gene as previously reported 31.…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, some case reports have described high-grade dysplasia or adenocarcinoma in association with FAP-associated FGP, suggesting that FAP-associated FGP is a potential premalignant lesion 29 30 31. As for genetic analysis, previous studies revealed the presence of somatic APC mutations in FAP-associated FGP, indicating neoplastic lesions caused by the inactivation of both alleles, similar to the mechanism of other FAP-associated neoplasms 28 32. Consistent with this, 1 patient with 2 noninvasive neoplasms in FGP who underwent proximal gastrectomy in our study had inactivation of the APC gene as previously reported 31.…”
Section: Discussionmentioning
confidence: 92%
“…Somatic, second-hit APC alterations precede morphologic dysplasia in many FAP-associated FGPs, indicating that FGPs arising in the setting of FAP are neoplastic lesions. 11 In contrast, sporadic FGPs without dysplasia have mutations in the gene encoding β-catenin ( CTNNB1 ) but lack APC alterations, 12 whereas sporadic FGPs with low-grade dysplasia display APC alterations but usually lack mutations in CTNNB1 . 13 …”
Section: Discussionmentioning
confidence: 99%
“…Although FGPs in the general population are typically benign lesions, up to 25% of those in FAP patients show foveolar dysplasia (41), and cases of gastric carcinoma associated with diffuse FGP have also been reported (42)(43)(44)(45). In a study of 41 FGPs from 17 FAP patients, 51% of polyps demonstrated an inactivating somatic APC gene alteration, whereas there were no such APC gene mutations in 13 sporadic FGPs used for comparison (46). There was no significant difference in mutation rate among FGPs with or without dysplasia (46).…”
Section: Upper Gastrointestinal Tract Polyps and Cancermentioning
confidence: 99%
“…In a study of 41 FGPs from 17 FAP patients, 51% of polyps demonstrated an inactivating somatic APC gene alteration, whereas there were no such APC gene mutations in 13 sporadic FGPs used for comparison (46). There was no significant difference in mutation rate among FGPs with or without dysplasia (46). These second-hit somatic APC gene alterations, superimposed on germline APC mutations, could account for the neoplastic potential of FGPs in FAP, which appear to be not only clinically, but also pathologically distinct from sporadic lesions.…”
Section: Upper Gastrointestinal Tract Polyps and Cancermentioning
confidence: 99%